Monitoring and targeting tumor growth and metastasis in vivo in mice using semiconductor quantum dots - Prieto, Eloise I.
This study investigates the utility of semiconductor quantum dots in monitoring and targeting tumor growth and metastasis in mice. Two quantum dot applications were evaluated: quantum dots as cell label to mark cancer cells prior to implantation and quantum dots as tumor-specific probes. In order to assess the first application, qunatum dots were used to label cancer cells prior to implantation in mice. The labeled cells were then implanted through systemic and local routes. Histological analysis of lungs and livers showed successful tracking and imaging of tumor metastasis in mice. Assessment of the second approach involved the conjugation of quantum dots to tumor-specific monoclonal antibody CC49. The resulting bioconjugate was then administered systemically to mice bearing tumors. Histological analysis of tumors and organs obtained from the mice revealed the absence of quantum dot fluorescence in the primary tumor and in areas of tumor metastasis. This observed lack of fluorescent signal was found to be due to strong tissue autofluoresecence as supported by biodistribution studies involving normal mice systemically administered with the bioconjugate. Histological data obtained revealed the lack of any QD-fluoresence as well as the absence of any difference between normal mice administered with the CC49-QD bioconjugate and mice without the bioconjugate. These results confirm the potential of using semiconductor quantum dots as a means of tracking tumor metastasis in vivo but systemic administration of QDs conjugated to antibodies require further refinement in the optics to discriminate between tissue autofluorescence and QD-conjugated antibodies fluorescing in the green wavelength.
Computer print out.
Keywords: Tumors -- Growth; Metastasis